Reconstructing Community Knowledge into Scientific Knowledge of Ecotourism at Lemor Botanical Garden and Lemor Spring Tourism - Thufail Mujaddid Al-Qoyyim; Wardi Kurniawan; Doni Kurniawan (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
This study examines the reconstruction of community knowledge into scientific knowledge related to ecotourism in Lemor Botanical Garden and Lemor Spring Tourism. The local community possesses a profound understanding of the conservation and ecological functions of these areas; however, a gap remains between local wisdom and scientific concepts. This research employs a qualitative case study approach, utilizing field observations, in-depth interviews, and documentation. The findings reveal that the community recognizes Lemor Botanical Garden as a center for the conservation of rare plant species, an educational site, and an environment-based ecotourism destination. Meanwhile, Lemor Spring Tourism is believed to offer health benefits and spiritual value, some of which can be scientifically explained through the mineral composition of the water and its balanced ecosystem. Certain traditional aspects, such as customary rituals and beliefs in misfortune, are more symbolic than scientifically grounded. The reconstruction of this knowledge is crucial for enhancing the sustainable management of these areas, optimizing the scientific potential of ecotourism, and improving community welfare through a conservation and sustainable tourism approach. Thus, the synergy between science and local wisdom can strengthen more effective and sustainable management strategies for both areas.